The Spillover Effect of Autonomy Frustration on Human Motivation and Its Electrophysiological Representation - Fang, Hui; Wan, Xiaoming; Zheng, Shuyue; Meng, Liang (Frontiers in Human Neuroscience, 2020)
It is a commonplace that some people may adopt a controlling style, which brings about autonomy frustration to others. Existing studies on autonomy frustration mainly examined its effect in the primary thwarting context, ignoring its potential spillover to subsequent activities. In this study, we examined whether prior autonomy frustration would have a sustaining negative impact on another autonomy-supportive activity that follows. In this electrophysiological study, participants worked on two irrelevant tasks organized by two experimenters. We adopted a between-group design and manipulated participants’ autonomy frustration by providing varied audio instructions during Session 1. In Session 2, all participants were instructed to complete a moderately difficult task that is autonomy-supportive instead, and we observed a less pronounced reward positivity (RewP) difference wave and a smaller P300 in the autonomy-frustration group compared with the control group. These findings suggest that the negative influence of autonomy frustration is longstanding and that it can undermine one’s motivation and attention in a following activity that is autonomy-supportive itself. Thus, our findings provided original neutral evidence for the adverse intertemporal effect of autonomy frustration, as well as important practical implications.